Autoantibody formation in patients with rheumatoid arthritis treated with anti-TNFα. Issue 3 (5th August 2004) - Eriksson, C; Engstrand, S; Sundqvist, K-G; Rantapää-Dahlqvist, S
Abstract : Background: Research on autoantibody formation in patients treated with TNFα inhibitors has produced contradictory results. Objective: To study the prevalence of autoantibodies in patients with rheumatoid arthritis treated with the TNFα inhibitor infliximab. Methods: 53 patients (48 female, 11 male) treated with infliximab for rheumatoid arthritis were followed for autoantibody production before treatment and after 14, 30, and 54 weeks. Six patients treated with etanercept were studied for comparison. The analyses included antibodies against nuclear antigens (ANA), extractable nuclear antigens, double stranded (ds)DNA (by ELISA, IIF on Crithidia luciliae for IgM and IgG, and Farr assay), nucleosomes, cardiolipin, smooth muscle, mitochondria, proteinase 3, and myeloperoxidase antigens. Results: The number of patients treated with infliximab who developed antibodies against dsDNA of both IgG and IgM class (tested by IIF) increased significantly. The prevalence of patients positive for IgG class increased to 66% at 30 weeks and 45% at 54 weeks, and of IgM class to 85% and 70%, respectively. The titre and number of patients expressing antibodies against nucleosomes and ANA also increased significantly. The number of rheumatoid factor or anticardiolipin positive patients was stable and there was no increase in antibodies against the other antigens. A lupus-like syndrome was seen in one patient. No patient treated with etanercept developed any of these autoantibodies. Conclusions: Patients treated with infliximab may develop anti-dsDNA antibodies of both IgM and IgG class, anti-nucleosome antibodies, and ANA, with a gradual increase until 30 weeks.